Trust in God: an evaluative review of the literature and research proposal - Hook, Joshua N. (Mental health, religion & culture, 2021)
Until recently, psychologists have conceptualised and studied trust in God (TIG) largely in isolation from contemporary work in theology, philosophy, history, and biblical studies that has examined the topic with increasing clarity. In this article, we first review the primary ways that psychologists have conceptualised and measured TIG. Then, we draw on conceptualizations of TIG outside the psychology of religion to provide a conceptual map for how TIG might be related to theorised predictors and outcomes. Finally, we provide a research agenda for future empirical work in this area, as well as practical applications for counsellors and religious leaders.